Delayed Surgery, Low Presurgery Activity, and Poor Preoperative IKDC Scores Are Correlated with Lower Rates of Return to Sports after ACL Reconstruction in an Asian Population - Lim, Dominic G.W.; Chou, Andrew C.C.; Chang, Paul C.C.; Tan, Edwin T.S.; Lie, Denny T.T. (The Journal of Knee Surgery, 2021)
There is limited literature regarding the early postsurgical outcomes of anterior cruciate ligament (ACL) reconstruction in Asian populations, particularly in the rates of return to sports. We aimed to quantify early clinical outcomes for ACL reconstruction, determine the predictive value of surgeon- and patient-reported outcomes on the rate of return to sports in the early postoperative period, and identify factors predictive of return to sports. We analyzed the data of 55 patients who underwent ACL reconstruction at our tertiary medical center from 2015 to 2016. All patients underwent transportal ACL reconstruction and a standardized post-ACL reconstruction rehabilitation protocol. Patients with concurrent meniscal injury and repair were included. Patients were evaluated at the 3-month, 6-month, 1-year, and 2-year postoperative periods. Surgeon- and patient-reported outcome scores were collected at each follow-up through a systematic questionnaire designed to determine the patient's level of return to sport and reasons for not returning. Surgeon- and patient-reported outcome measures improved significantly over the 2-year postoperative period (p < 0.001). Overall rate of return to sports was 58.2%. The International Knee Documentation Committee (IKDC) subjective (p = 0.02), symptomatic (p = 0.001), composite (p = 0.005), Tegner (p < 0.001) and Lysholm (p = 0.049) scores at 2-year follow-up were significantly worse in patients who failed to return to sports. Earliest difference in scores manifested at 3-month postsurgery (p = 0.011). IKDC grade-D patients were 18.1 times less likely to return to sports (p = 0.035). Delayed surgery (p = 0.01) and presurgery inactivity (p = 0.023) were negatively predictive of return to sports. The rate of return to sport is consistent with the literature analyzing other ethnic populations. Both surgeon- and patient-reported outcome scores at 2-year postsurgery exhibited significant differences between those who did and did not return to sports. Patients should be advised to seek surgical treatment as soon as possible and stay active preoperatively to maximize return to sports.
Keywords: return to sports; ACL reconstruction; patient-reported outcome measures